KINERJA PEGAWAI DI SEKRETARIAT DAERAH KABUPATEN KUANTAN SINGINGI - Zulkarnain, Tiwi; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Performance is the result of work in the quality and quantity achieved by an employee in carrying out their duties. Employee performance is a very important activity because it can be used as a measure of the organization's success in achieving the organization's vision and mission. The performance of employees at the Kuantan Singingi District Head Office is still experiencing various problems that can be seen from lack of discipline of employees, the large number of employees postponing official duties and there are still many officials who do not understand the main tasks and functions. This study aims to determine the performance of employees at the Kuantan Singingi District Regent's office and to identify factors that hinder the performance of employees in the Kuantan Singingi District Regent's office. This research uses descriptive qualitative methods. This method uses the theory of performance by Bernardin and Russel in Burso (2018) with indicators of Quality, Quantity, Timeliness, Effectiveness, Independence, Work Commitment. From the results of the study it was found that the performance of employees in the Kuantan Singingi Regency Regent's office was not maximal, seen through some of these performance indicators, one of them is in terms of the quality of employee performance, which is still 25% that has been achieved well, approximately 75% the quality of employee performance has not been achieved or not good. As for the causes of the performance of Kuantan Singingi Regency government employees have not been maximized, among others, due to employee discipline, limited human resources, and limited facilities and infrastructure. Therefore, so that the employee's performance becomes maximal, it is necessary to provide strict sanctions against employees who are not disciplined, increase in the number of employees, and the addition of facilities and infrastructure to support the entire work of employees in the Kuantan Singingi Regency government environment. Keywords: Performance, Employee